Argamassa com agregado reciclado de resíduo de construção e demolição : propriedades mecânicas e fixação de carbono - Borges, Pietra Moraes (2022)
Over the past few years, the use of recycled aggregate (RA) from construction and demolition waste (CDW) has proved to be a promising alternative for increasing the concept of circular economy within the construction industry. The use of RA contributes to a more adequate destination of these wastes besides minimizing the use of natural aggregates (NA). Carbonation also has proved to be a promising alternative to carbon capture, use, and storage. This present work aims to evaluate the substitution influence of NA for RA. For that, mortar specimens were molded with replacement levels of 0, 25, 50, 75, and 100% of the NA for RA, and three different granulometries were used to evaluate the particle size influence. To analyze the performance of these modifications, compressive strength and tensile strength in flexion, porosity, absorption, and bulk density were performed to evaluate physicalmechanical properties. To assess the influence in microstructural properties X-ray microtomography test was carried out in addition to XRD analysis. With the purpose to evaluate uptake, carbonation depth and thermogravimetry were made from accelerated carbonation tests. The results showed that mortars with 25% have the least emissive balance and that the replacement level increases the amount of CO2 captured. Particle size distribution also influences significantly in the results. Further, all samples had satisfactory mechanical behavior according to Brazilian Standards.